Tingkat Pengetahuan Ibu tentang Sinusitis di Dusun VII Desa Sei Mencirim Kecamatan Kutalimbaru Kabupaten Deli Serdang - Katini Katini; Ade Irma Triana Siregar (Jurnal Riset Hesti Medan, 2022)
Sinusitis is a disease that occurs in the sinus area. The sinuses are air cavities that are in the area of the face connected to the nose. The function of the sinus cavity itself is to keep the nose moist and maintain air exchange in the nasal area. The research design used in this study is descriptive quantitative in nature aiming to determine the mother's level of knowledge about sinusitis. Sampling was carried out using "purposive sampling", which is a sampling technique based on certain considerations made by the researchers themselves, based on previously known characteristics or characteristics of the population. So that the sample in this study amounted to 60 respondents. And the samples taken are samples that have criteria, namely mothers who have children, mothers aged 27-40 years and mothers who are willing to be respondents. From the research results it is known that based on age, knowledge is generally sufficient, this is because respondents received counseling from health workers by 40 (80%), while 20 people (20%) were not good. In this case, people who experience or suffer from this disease will understand more about sinusitis. Based on education that 26 people (43.3%) have good knowledge, 29 people (48.33%) have sufficient knowledge and 5 people have less knowledge (8.33%). Based on work, it is known that there are 6 mothers (10%) who have good knowledge, 19 people (31.66%) have sufficient knowledge and 35 people (58.3%) lack knowledge. Based on information sources, there are 9 mothers who have good knowledge (15.00). %), enough for 17 people (28.33%) and less for 34 people (56.67%). Mother's level of knowledge about sinusitis in Dusun VII Sei Mencirim Village, Kutalimbaru District as a whole, there were 43 respondents who had sufficient knowledge (71.67%) and who had less knowledge, there were 17 people (28.33%). This is because health workers do not conduct counseling in every family and they are reluctant to work directly in the community.